Solar System Education Application Using Markerless Augmented Reality (AR) on The Android Platform - Harchristanto, Bagas Afrian; Utami, Wahyu Sri (International Journal Software Engineering and Computer Science (IJSECS), 2023)
The solar system, a small component of the vast universe, encompasses celestial bodies including the Sun, its planets - Mercury, Venus, Earth, Mars, Jupiter, Saturn, Uranus, and Neptune - along with 165 identified satellites. Many students find solar system studies engaging, as it enables understanding of the myriad celestial objects beyond our planet. Traditional learning methods, often limited to explanations and exercises by instructors, require students to be attentive and diligent in reading to master the subject. However, this can sometimes lead to monotony and disinterest. Previous research indicates that the use of educational media is a key factor in successful learning activities. Technology-based education systems make learning more dynamic and interesting by incorporating images, text, sound, and video. Augmented Reality (AR), which merges real objects with virtual elements in an interactive environment, allows virtual technology to appear seamlessly in the real world. This creates an illusion of virtual objects being present in front of the user, enhancing realism. Recent studies have resulted in the development of an AR application for learning and understanding the Milky Way galaxy's solar system. This application addresses the lack of comprehension in primary school students who traditionally use globes and pictures for solar system education. It operates without the internet, modernizing learning and capturing students' interest through its Android application format. The application functions optimally on Android devices with a minimum of 3GB RAM, performing more efficiently on devices exceeding these specifications.